ПРОЕКТИРОВАНИЕ И ЭКСПЕРИМЕНТАЛЬНЫЕ ИССЛЕДОВАНИЯ СТАЛЕФИБРОБЕТОННОЙ ПЛИТЫ ПЕРЕКРЫТИЯ (World Science, 2018)
In the work, the design of the floor slab with five voids of steel fiber concrete, similar to a serial reinforced concrete slab, is proposed. Both plates are calculated in accordance with the regulations on the first and second limiting states. For experimental studies, a series of plates was made, each of which was tested before destruction. Scaling was used for all the plates, taking into account the design standards and technological capabilities of the laboratory.The loading of structures during testing was carried out in steps. Each step was 10% of the control load when checking the bearing capacity and crack resistance and 20% of the control load when checking the rigidity of structures. As a result of tests, the values of stresses and deflections were obtained as in theoretical calculations, the stresses in the concrete and steel fiber concrete slabs differ only slightly, and the deflections, especially up to 60% of the breaking load, differ several times, which confirms the much slower crack opening in the steel fiber concrete slabs. This suggests that at loads corresponding to the operational level, cracks will not open. The use of steel fiber concrete with preservation of linear reinforcement for the manufacture of hollow-core slabs allows to improve their characteristics, first of all - bearing capacity and crack resistance.